2014
DOI: 10.1364/oe.22.011797
|View full text |Cite
|
Sign up to set email alerts
|

Role of resonance absorption in terahertz radiation generation from solid targets

Abstract: The interaction of 100-fs laser pulses with solid targets at laser intensities 10(16)-10(18)W/cm(2) has been investigated experimentally by simultaneous measurements of terahertz (THz) and second harmonic signals. THz yield at the front side of the target, which rises from the self-organized transient electron currents along the target surface, is found scaling linearly with the laser intensity basically. Measurements of specularly reflected light spectrum show clear evidence of resonance absorption. The posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…All these properties agree with CTR depicted above. By using lasers with different polarizations and contrast ratios, Li et al 6,32,33 revealed the significance of hot electrons, especially the role of resonance absorption, to the generation of THz radiation.…”
Section: E Comparison With Some Experimental Observationsmentioning
confidence: 99%
“…All these properties agree with CTR depicted above. By using lasers with different polarizations and contrast ratios, Li et al 6,32,33 revealed the significance of hot electrons, especially the role of resonance absorption, to the generation of THz radiation.…”
Section: E Comparison With Some Experimental Observationsmentioning
confidence: 99%
“…Unlike terahertz emission from the target front surface where the NIR laser pulse interacts with the solid foil, the generation of coherent terahertz radiation from the rear surface is different. In the case of emission from the target front surface, there are a multitude of physical processes responsible for terahertz generation from the laser-plasma interaction region [23][24][25][26][27][28] which are directly dependent on the incident laser parameters (polarization, ASE contrast, pulse duration, intensity) and target material etc. However, in the case of emission from the rear surface [7,8,[29][30][31][32][33][34] the THz dynamics has to depend on the hot electrons which are generated at the front surface during the interaction of laser pulse with the foil and gain energy and accelerated back to the target ballistically, travel through the target and exit the rear surface.…”
Section: Thz Generation At the Target Rear Surfacementioning
confidence: 99%
“…In experiments we have also measured the spectra of scattered laser light. The THz radiation near the target surface is found to be correlated with the second harmonics of the laser pulse [40,42], while the radiation near the target normal shows positive correlation with three-halves harmonics [38].…”
Section: Target Surface Transient Currentmentioning
confidence: 99%